A review of emergency management governance at construction sites in Malaysia - Khairilmizal Samsudin; Nurulilyana Sansuddin; Maliki Hapani; Mohamad Fahmi Hussin; Ainul Husna Kamarudin; Ahmad Faizol Hashim (Penerbit Universiti Kebangsaan Malaysia, 2023)
The construction industry is one of the biggest industries in Malaysia which contribute to a significant growth towards the country’s economy. Accidents, disasters, or crisis events originating either from internal or external of the construction site can cause delays to the project and impact the continuity and productivity of the overall project, hence there is a need for emergency management capability to be available for each construction site. Hence, it is the objective of this research is to identify and review current emergency management governance in construction industries in Malaysia and indicate the compliance of the governance towards Malaysia’s disaster management environment. In understanding disaster governance of emergency management in Malaysia at the construction site and in the construction industry, a systematic procedure for reviewing and evaluating documents which include both printed and electronic materials was conducted. This study concentrates on both the content validity method and face validity method. Identify significant documents were studied and recorded to acknowledge the contribution and support that the document provides towards disaster management and validation of findings from subject matter experts in the industry. Findings indicate that there is still a huge gap in the construction industry emergency management and governance in emergency management is greatly needed in ensuring the high productivity and sustainability of the construction industry.